Model pembelajaran matematika realistik berbasis teori bruner untuk meningkatkan kemampuan berpikir kritis matematis pada materi bangun datar siswa smp - Desi Trisusanti; Evan Farhan Wahyu Puadi; Uba Umbara (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
Desi Trisusanti (NIM:153223018), Realistic Mathematics Education Based on Bruner’s Theory to Improve Critical Thinking Mathematically geometry of square At Junior High School Students Build Materials (Classroom Action Research at SMPN 2 Cimahi Grades 7B), Department of Mathematics (PMTK), 2017. Capabilities Critical thinking is very important to be possessed by learners. Critical thinking is applied to learners to learn to solve problems systematically, innovatively and designing fundamental solutions. Improvement of critical thinking skills is done through a meaningful learning process for learners. A knowledge will be meaningful for learners if the learning process is implemented in a context or learning using realistic problems. This study aims to improve the critical thinking skills of class 7B students on the material geometry of square through Realistic Mathematical Learning Model-Based Mathematical Learning. This research is a classroom action research with research objects 7B grade students of SMPN 2 Cimahi 2nd semester in the academic year 2016/2017 as many as 26 people. The study was conducted in two cycles, each cycle consisting of 4 stages of planning, action, observation and reflection. The indicator of success of this research is the percentage of critical thinking ability based on KKM more than 71.5% are in high to very high category, Percentage of critical thinking ability of individual mathematical experience from cycle 1 to cycle 2, percentage of classical learning completion at least 80% Students of realistic mathematics learning model based on Bruner's theory are in good category up to very well. Based on the analysis of research data, cycle 1 percentage critical thinking skills of learners reached 69.95% in middle category and the percentage of classical learning completeness reached 69.23%. While on the second cycle of the percentage of the critical thinking skills of students is reached 75.18% at the high category 5:23% or an increase of cycle 1. Percentage of classical learning completeness in cycle 2 reached 84.62%, an increase of 15:39% of cycle 1. Response Learners toward Learning Mathematical Model Realistic-Based Theory Bruner is on the rise and is in good category. From these results it can be concluded that the Realistic Mathematics Instructional Model-Based Theory of Bruner can improve critical thinking skills on the material flat wake mathematical learners 7B classroom SMPN 2 Cimahi.